I want a better catastrophe : navigating the climate crisis with grief, hope, and gallows humor : an existential manual for tragic optimists, can-do pessimists, and compassionate doomers - Boyd, Andrew, 1962- (New Society Publishers, 2023)
"Reeling from a crisis of hope, lifelong activist Andrew Boyd seeks out today's leading climate thinkers, from collapse-psychologist Jamey Hecht to Indigenous botanist Robin Wall Kimmerer. "If it's the end of the world, now what?" he asks, as he steers us through our climate angst in search of a "better catastrophe.""--